Doing Participatory Research with Families that Live in Poverty: the Process, Potential and Limitations - Panciroli, Chiara; Corradini, Francesca (Participatory Social Work: Research, Practice, Education, 2019)
The contribution discusses a practical application of the participatory research approach in the field of poverty. The research was implemented with a high degree of participation, and the collaboration of some families who were living in a marginalized neighbourhood of Reggio Emilia, a small city in Northern Italy. In the contribution, the potentialities and limits of this approach are presented. In particular, the benefits from the perspectives of all participants are described and analysed. The research process contributed to strengthening the co-researchers’ capabilities and raised their consciousness. In conclusion, a description of the usefulness and added value that participatory research provides to the field of social work and the future of research in this field is given.